Current and emerging therapies for endometriosis-associated pain: a review - Ebunoluwa Oluwatimileyin Tijani; Lydia Oluwatoyin Ajayi; Oladimeji Samson Tijani; Oyedayo Phillips Akano; Ayodeji Folorunsho Ajayi (Middle East Fertility Society Journal)
Abstract Background Endometriosis is a severe gynaecological disease marked by the formation of endometrial-like growth beyond the uterus, which causes severe pelvic pain, infertility, and a reduced standard of life. Despite the progress that has been made in understanding its aetiology, the treatment remains difficult due to the disease's complicated structure and diversity in different patient responses. Main body. This narrative review examines both present and emerging therapeutics for endometriosis-related pain, focusing on pharmaceutical, surgical, and complementary treatment options. Current pharmacological treatments, such as nonsteroidal anti-inflammatory medications (NSAIDs), hormone therapy, and analgesics, provide symptom alleviation but are frequently limited due to side effects and long-term effectiveness issues. Surgical procedures, such as laparoscopy and nerve ablation, provide alternatives, although recurrence rates remain high. Additionally, complementary therapies such as acupuncture and physical therapy are gaining recognition for their role in pain management. The review also explores emerging therapies, including novel pharmacological approaches like selective progesterone receptor modulators (SPRMs), aromatase inhibitors, and gene-based therapies. Advances in minimally invasive surgical techniques and regenerative medicine, such as stem cell therapies, are also discussed. Conclusion An essential comparison of these methods of therapy highlights the need for personalised approaches and further research to address variation of the disease. The review concludes with recommendations for subsequent studies, emphasising the need for long-term studies, real-world data, and innovations in pain management that integrate multifaceted therapies. This analysis aims to provide healthcare providers with a clearer understanding of the changing landscape of endometriosis treatment.